The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3144/expresspolymlett.2012.85
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanocellulose isolation techniques on the formation of reinforced poly(vinyl alcohol) nanocomposite films

Abstract: Abstract. Three techniques including acid hydrolysis (AH), 2,2,6,6-tetramethylpiperidine-1-oxyl radical (TEMPO)-mediated oxidation (TMO) and ultrasonication (US) were introduced to isolate nanocellulose from microcrystalline cellulose, in order to reinforce poly(vinyl alcohol) (PVA) films. Important differences were noticed in fiber quality of nanocellulose and film properties of PVA nanocomposite films. The TMO treatment was more efficient in nanocellulose isolation with higher aspect ratio, surface charge (-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(94 citation statements)
references
References 24 publications
4
79
0
3
Order By: Relevance
“…This result is similar to those reported for palm tree cellulose (84%) ) and microcrystalline cellulose (86%) hydrolyzed by FeCl3 in HCl acidic medium but under higher temperature (91 to 98 o C) and longer hydrolysis duration (4 to 6 h) at optimum hydrolysis conditions. However, all the nanocellulose yields prepared via Cr(III)-and Mn(II)-catalyzed hydrolysis under mild reaction were much more higher than the value reported for the hydrolysis of cellulosic materials including rice straw cellulose (16.9%) (Jiang and Hsieh 2013), microcrystalline cellulose (28.6%) (Zhou 2012), and bamboo bleached fiber (30%) (Brito et al 2012) via H2SO4 (~65 wt.%) hydrolysis procedure. A recent study (Tang et al 2015) conducted by Tang's group found that the yield of nanocellulose produced via phosphoric acid hydrolysis followed by enzymatic hydrolysis was only able to achieve a yield of 23.98% with a crystallinity of 57.8%.…”
Section: Fig 2 Xrd Patterns Of Native Cellulose Mn(ii)- and Cr(iimentioning
confidence: 71%
See 1 more Smart Citation
“…This result is similar to those reported for palm tree cellulose (84%) ) and microcrystalline cellulose (86%) hydrolyzed by FeCl3 in HCl acidic medium but under higher temperature (91 to 98 o C) and longer hydrolysis duration (4 to 6 h) at optimum hydrolysis conditions. However, all the nanocellulose yields prepared via Cr(III)-and Mn(II)-catalyzed hydrolysis under mild reaction were much more higher than the value reported for the hydrolysis of cellulosic materials including rice straw cellulose (16.9%) (Jiang and Hsieh 2013), microcrystalline cellulose (28.6%) (Zhou 2012), and bamboo bleached fiber (30%) (Brito et al 2012) via H2SO4 (~65 wt.%) hydrolysis procedure. A recent study (Tang et al 2015) conducted by Tang's group found that the yield of nanocellulose produced via phosphoric acid hydrolysis followed by enzymatic hydrolysis was only able to achieve a yield of 23.98% with a crystallinity of 57.8%.…”
Section: Fig 2 Xrd Patterns Of Native Cellulose Mn(ii)- and Cr(iimentioning
confidence: 71%
“…An absolute value lying within 0 to ± 15 mV reflects the onset flocculation and agglomeration of nanocellulose (Zhou 2012), whereas the values greater (or lower) than ± 25 mV were generally considered to be relatively stable for mutual repulsion to form a good stability colloidal suspension . In this study, the zeta potential for Mn(II)-and Cr(III)-treated nanocellulose was about ─42.5 and ─44.9 mV, respectively in the aqueous suspensions, thus indicative of the possibility to produce rather stable colloidal suspensions due to sufficient repulsive force.…”
Section: Particle Size Analysis (Dls) and Zeta Potential Analysismentioning
confidence: 99%
“…Another drawback using nanocellulose fibers is the difficulty to disperse them uniformly in non-polar medium because of their polar surface (Oksman et al 2006). So, most researchers are focused on a water-soluble polymeric matrix, considering the hydrophilic character of cellulose for the easier dispersion of cellulose (Oksman et al 2006;Bondeson and Oksman 2007;Chen et al 2009;Alain Dufresne 2010;Lemahieu et al 2011;Zhou et al 2012;Tang et al 2015;Pracella et al 2014;Trifol et al 2016;Haafiz et al 2016;Ivdre et al 2016;Khoo et al 2016;Sethi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The CNCs were isolated from the cotton linters through acid hydrolysis as previously mentioned (Zhou et al 2012). The cotton linters were immersed in 64 wt.% sulfuric acid solution with a ratio of 1 g/mL to 8.75 g/mL at 45 °C under strong continuous stirring for 1.5 h. The obtained hydrolyzed cellulose was repeatedly washed, via centrifugation (10000 rpm, 10 min) at least 3 ×, and dialyzed against deionized water until the pH of the suspension was near neutral.…”
Section: Preparation Of Cncmentioning
confidence: 99%
“…The heating rate of the films was fairly fast, and the ∆T reached an equilibrium state within 20 s. The temperature equilibrium of AuNPs in the matrix is dominated by the thermodynamic equilibrium process, including a heat-absorbing process caused by the photothermal effect of AuNPs and a heat-losing process such as convection, conduction, etc. (Zhou et al 2012). When the two processes are unbalanced, the ∆T presents either increases or decreases.…”
mentioning
confidence: 99%